Development and Resolution of Secondary Adrenal Insufficiency after an Intra-Articular Steroid Injection. (22nd December 2022) - Tan, Jia Wei; Majumdar, Sachin K.
Abstract : Corticosteroid injections are commonly indicated in inflammatory conditions involving the soft tissues, tendon sheaths, bursae, and joints. Local corticosteroids carry a lower risk of complications than systemic corticosteroid but may be systemically absorbed and subsequently suppress the hypothalamic-pituitary-adrenal (HPA) axis. This can cause secondary adrenal insufficiency (SAI) as well as iatrogenic Cushing's syndrome. We report a 78-year-old female who presented with nonspecific gastrointestinal symptoms after a recent intra-articular steroid injection in her shoulder. She had hyponatremia, low morning cortisol, and failed to respond to high-dose cosyntropin. Further workup revealed the underlying cause to be SAI. Follow-up testing revealed a recovery of HPA responsiveness within 2 weeks of her initial diagnosis. Conclusion . Our case highlights how the hypothalamic-pituitary axis (HPA) can be suppressed with intra-articular steroids. The threshold to test corticosteroid users for adrenal insufficiency should be low in clinical practice, especially for those patients with nonspecific symptoms after steroid injections. Once diagnosed, temporary treatment with steroids may be required.